PENGARUH BELANJA PEMERINTAH DAERAH TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Simanjuntak, Gloria Yemima; Maya Yulika; Dewi Nopika Putri; Wahjoe Pangestoeti (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Regional government spending plays a crucial role in driving sustainable economic growth in Indonesia, particularly within the framework of fiscal decentralization. This study analyzes the impact of different expenditure components including direct and indirect expenditures, capital spending, education, and health on economic growth using a quantitative approach based on panel data and time series analysis. The findings reveal that direct and capital expenditures have a positive and significant effect on economic growth. In contrast, indirect spending and social expenditures such as education and health do not exhibit a strong direct impact, although they are still considered crucial for long-term development outcomes. Regional disparities in impact highlight the importance of fiscal capacity and sound budget management. Moreover, the quality of human capital plays a pivotal role in amplifying the effectiveness of public spending in promoting inclusive development. These findings underscore the necessity for regional fiscal reforms that prioritize efficiency, long-term planning, and the integration of infrastructure investment and human capital development.